Exploring and understanding delirium: a comprehensive narrative review with emphasis on neurological disorders - Arpan mitra; Niraj Kumar Srivastava; ankur vivek; Nayana Bhuyan; Rukhsar Parveen; Vijaya Nath Mishra; Abhishek Pathak (The Egyptian Journal of Internal Medicine, 2026)
Abstract A narrative review was presented, synthesizing existing literature on the historical understanding, neurobiological mechanisms, diagnostic approaches, and treatment modalities related to delirium. The purpose of this narrative review is to provide an updated overview of delirium, emphasizing its complex pathophysiology, clinical characteristics, risk factors, diagnostic challenges, and management strategies, particularly in patients with neurological disorders. Delirium predominantly occurs in hospitalized patients, especially those with pre-existing neurological conditions. Its pathogenesis is multifactorial, involving neuroinflammatory processes, neurotransmitter imbalances, and disruptions in neural connectivity. Clinically, it presents with acute onset of altered mental status, inattention, disorganized thinking, and fluctuating consciousness. Crucial risk factors include advanced age, cognitive impairment, polypharmacy, metabolic disturbances, and critical illness. Diagnosis remains challenging due to heterogeneous manifestations and symptom overlap with other disorders. Current diagnostic strategies integrate standardized screening tools, clinical assessment, and biomarker research. Management primarily targets underlying causes, supportive care optimization, and cautious pharmacological use. Delirium represents a multifaceted neuropsychiatric syndrome closely linked to neurological diseases and adverse patient outcomes. Persistent challenges in its prevention, diagnosis, and management highlight the need for a deeper understanding of its mechanistic pathways and risk factors to inform targeted therapeutic interventions and improve clinical outcomes.